Hypoglycemic effects of Berberis aristata and Tamarindus indica extracts in vitro - Mangesh A. Bhutkar; Somnath D. Bhinge; Dheeraj S. Randive; Ganesh H. Wadkar (Faculty of Pharmacy, Cairo University, 2017)
Objective: The objective of the present investigation was to evaluate the hypoglycemic potential of Berberis aristata and Tamarindus indica using various in vitro techniques. Methods: The selected plant extracts were studied for their effects on glucose adsorption capacity, in vitro glucose diffusion, in vitro amylolysis kinetics and glucose transport across the yeast cells. Results: It was observed that both the plant extracts adsorbed glucose and the adsorption of glucose increased remarkably with an increase in glucose concentration. No significant (p ⩽ 0.05) differences were observed between the adsorption capacities of B. aristata and T. indica. The results of amylolysis kinetic experimental model exhibited that the rate of glucose diffusion was increased with time from 30 to 180 min and both the plant extracts demonstrated significant inhibitory effects on movement of glucose into external solution across dialysis membrane as compared to control. It was observed that the plant extracts also promoted glucose uptake by the yeast cells. Enhancement of glucose uptake was dependent on both the sample and glucose concentration. B. aristata extract exhibited significantly higher (p ⩽ 0.05) activity than the extract of T. indica at all concentrations. Conclusion: The results of the study verified the hypoglycemic activity of the extracts of B. aristata and T. indica. However, the observed effects need to be confirmed using different in vivo models and clinical trials for their effective utilization as therapeutic agents.